Praxeological analysis in Indonesian and Singaporean mathematics textbooks: An understanding geometrical similarity by students - Kuncoro, Krida Singgih; Suryadi, Didi; Dahlan, Jarnawi Afgani; Jupri, Al (Journal on Mathematics Education, 2024)
Mathematics textbooks are essential tools for facilitating the achievement of learning objectives, yet their use varies across classrooms, even when the same mathematical concepts are being taught. This study aims to investigate students' understanding of geometrical similarity through praxeological analysis within the framework of the Anthropological Theory of the Didactic (ATD). The analysis identifies differences in the structuring of geometrical similarity tasks between Indonesian and Singaporean textbooks. According to ATD praxeology, mathematical content is analyzed through the "praxis" and "logos" blocks, where praxis encompasses task types (T) and techniques (τ), while logos involves technology (θ) and theory (Θ). The findings highlight distinct priorities in how geometrical similarity is presented in textbooks from both countries, with implications for students’ conceptual and procedural understanding. Specifically, the absence of pantograph tasks in Singaporean textbooks and the lack of scale factor exercises in Indonesian textbooks reflect differences in knowledge construction and task emphasis. These variations impact students' ability to relate textbook knowledge to real-world applications. The study underscores the significance of incorporating a diverse range of task designs and practical experiences to enhance students' geometric reasoning abilities. A well-structured textbook not only supports students in achieving learning objectives but also fosters a continuous process of building, connecting, and deepening their mathematical understanding.